ANALISIS PROSES PEMBERIAN KREDIT PADA BANK RAKYAT INDONESIA (BRI) CABANG BITUNG - Supit, Wandha Marina; Nangoi, Grace B; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2021)
This study aims to analyze the process of granting credit to the Bank Rakyat Indonesia (BRI) Bitung branch. This research is a qualitative research with an exploratory approach. Data obtained through in-depth interview techniques, observation and documentation study.The results showed that the provision of credit at the Bank Rakyat Indonesia (BRI) Bitung branch has followed the existing rules and regulations. The basic of the rule and regulations imposed by Bank Rakyat Indonesia (BRI) Bitung branch, namely by applying the basic principles of credit, namely character, capacity, capital, collateral and condition of economic. However the problem that arises in lending activities at Bank Rakyat Indonesia (BRI) Bitung branch is bad credit where the debtors cannot pay their obligations. The bacd credit problem had an impact on Bank Rakyat Indonesia (BRI) Bitung branch, especially on financial performance. And efforts to solve these problems the Bank Rakyat Indonesia (BRI Bitung branch provides credit rescue to the debtors.